CHARACTERIZATION AND IDENTIFICATION OF CELLULOLITIC PROBIOTIC BACTERIA ISOLATE FROM THE LARGE INTESTINE OF BALI PIG - L. H. F., Ibrahim; Cakra, I G. L. O.; Mudita, I M. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This research aims to identify and characterize superior cellulolytic bacterial isolates from Bali pig. This research was conducted at the Animal Feed and Nutrition Laboratory, Faculty of Animal Husbandry, Udayana University and this research was carried out for 4 months. This research was carried out using a survey method on bacterial isolates coded A5, A11, B2, C11. The variables observed in this study were cell morphology, colony morphology, catalase, oxygen demand, and the ability to sugars fermentation. The results of this study showed that the isolates of cellulolytic bacteria from the large intestine of Bali pigs which were coded A5, C11, B2, A11 had various cell morphologies, in terms of cell morphology, all isolates had stem or bacillus shapes and all isolates also had gram-positive properties. Likewise with the morphology of the colonies which have uniform properties such as smooth edges, rounded shapes, and overall milky white color. With catalase properties, all isolates are uniformly positive and these bacterial isolates does not require oxygen for their growth mechanism or have anaerobic properties. After analyzing the type of cellulolytic bacterial isolates, this type of Bacillus Licheniformis has a probability percentage of 97% in isolates A5 and B2, and isolates C11 and A11 have a type of Bacillus Lentus which has a probability percentage of 87%. All of the properties and characters of this cellulolytic bacterial isolate from Bali pigs are believed to be bacteria that degrade cellulose.